Analysis of Student Engagement: ECE Educators Teaching Skills Strengthening Courses in Distance Education - Siti Aisyah; Widiasih; Sandra Sukmaning Adji; Andayani; Suryo Prabowo; Siti Hadianti; Zakirman (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
Early childhood teacher education programs must figure out how to effectively educate the workforce as classrooms become more diverse due to children varied cultural backgrounds and skills. This study aims to analyse student involvement in the Strengthening of Early Childhood Educators Teaching Skills course in distance education. The research method used is descriptive qualitative. The research participants were 405 students of the Department of Early Childhood Education, consisting of 90% women aged between 20-55 years and an average age of 31 years. The research findings show that at the level of academic challenge, most students agree that the ECE Educators Teaching Skills Strengthening (TSS) course brings new ideas and certain experiences and is very helpful in applying theory or concepts to practical problems. Indicators of active/collaborative learning indicate that hands-on experiences help students work more effectively with others. Meanwhile, the student-faculty interaction component shows that they have carried out two-way discussions regarding material assessment and practice. Additionally, online tutorials have provided quick feedback on assignments and guidance in compiling practice reports. The student learning experience is greatly helped by the TSS course. Students acquire new knowledge and skills to support their profession as teachers. Keywords: early childhood educators, engagement, teaching skill, distance education References: Ackerman, D. J. (2004). What do teachers need? Practitioners’ perspectives on early childhood professional development. Journal of Early Childhood Teacher Education, 24(4), 291–301. https://doi.org/10.1080/1090102040240409 Bolliger, D. U., & Martin, F. (2018). Instructor and student perceptions of online student engagement strategies. Distance Education, 39(4), 568–583. https://doi.org/10.1080/01587919.2018.1520041 Cherrington, S., & Thornton, K. (2013). Continuing professional development in early childhood education in New Zealand. Early Years, 33(2), 119–132. https://doi.org/10.1080/09575146.2013.763770 Duhn, I., Fleer, M., & Harrison, L. (2016). Supporting multidisciplinary networks through relationality and a critical sense of belonging: Three ‘gardening tools’ and the Relational Agency Framework. International Journal of Early Years Education, 24(3), 378–391. https://doi.org/10.1080/09669760.2016.1196578 Fredricks, J. A., Blumenfeld, P. C., & Paris, A. H. (2004). School Engagement: Potential of the Concept, State of the Evidence. Review of Educational Research, 74(1), 59–109. https://doi.org/10.3102/00346543074001059 Fredricks, J., Filsecker, M. K., & Lawson, M. A. (2016). Student engagement, context, and adjustment: Addressing definitional, measurement, and methodological issues. Learning and Instruction, 43, 1–4. Hollis, L. P. (2018). Ghost-Students and the New Wave of Online Cheating for Community College Students. New Directions for Community Colleges, 2018(183), 25–34. https://doi.org/10.1002/cc.20314 Jensen, B., Holm, A., & Bremberg, S. (2013). Effectiveness of a Danish early year preschool program: A randomized trial. International Journal of Educational Research, 62, 115–128. https://doi.org/10.1016/j.ijer.2013.06.004 Jensen, B., Jensen, P., & Rasmussen, A. W. (2017). Does professional development of preschool teachers improve children’s socio-emotional outcomes? Labour Economics, 45(C), 26–39. Jensen, P., & Rasmussen, A. W. (2019). Professional Development and Its Impact on Children in Early Childhood Education and Care: A Meta-Analysis Based on European Studies. Scandinavian Journal of Educational Research, 63(6), 935–950. https://doi.org/10.1080/00313831.2018.1466359 Kang, M., & Im, T. (2013). Factors of learner–instructor interaction which predict perceived learning outcomes in online learning environment. Journal of Computer Assisted Learning, 29(3), 292–301. https://doi.org/10.1111/jcal.12005 Kim, H., Sefcik, J. S., & Bradway, C. (2017). Characteristics of Qualitative Descriptive Studies: A Systematic Review. Research in Nursing & Health, 40(1), 23–42. https://doi.org/10.1002/nur.21768 Kim, S., Raza, M., & Seidman, E. (2019). Improving 21st-century teaching skills: The key to effective 21st-century learners. Research in Comparative and International Education, 14(1), 99–117. https://doi.org/10.1177/1745499919829214 Martin, F., Wang, C., & Sadaf, A. (2018). Student perception of helpfulness of facilitation strategies that enhance instructor presence, connectedness, engagement and learning in online courses. Internet and Higher Education, 37(1), 52–65. Moore, M. G., & Kearsley, G. (2011). Distance Education: A Systems View of Online Learning. Cengage Learning. https://books.google.co.ls/books?id=dU8KAAAAQBAJ Muir, T., Milthorpe, N., Stone, C., Dyment, J., Freeman, E., & Hopwood, B. (2019). Chronicling engagement: Students’ experience of online learning over time. Distance Education, 40(2), 262–277. https://doi.org/10.1080/01587919.2019.1600367 Nguyen, T. D., Cannata, M., & Miller, J. (2018). Understanding student behavioral engagement: Importance of student interaction with peers and teachers. The Journal of Educational Research, 111(2), 163–174. https://doi.org/10.1080/00220671.2016.1220359 Quin, D. (2017). Longitudinal and Contextual Associations Between Teacher–Student Relationships and Student Engagement: A Systematic Review. Review of Educational Research, 87(2), 345–387. https://doi.org/10.3102/0034654316669434 Schachter, R. E. (2015). An Analytic Study of the Professional Development Research in Early Childhood Education. Early Education and Development, 26(8), 1057–1085. https://doi.org/10.1080/10409289.2015.1009335 Shackelford, J. L., & Maxwell, M. (2012). Sense of community in graduate online education: Contribution of learner-to-learner interaction. The International Review of Research in Open and Distributed Learning, 13(4), 228. https://doi.org/10.19173/irrodl.v13i4.1339 Tuovinen, J. E. (2000). Multimedia Distance Education Interactions. Educational Media International, 37(1), 16–24. https://doi.org/10.1080/095239800361473 Vlachopoulos, D., & Makri, A. (2019). Online communication and interaction in distance higher education: A framework study of good practice. International Review of Education, 65(4), 605–632. https://doi.org/10.1007/s11159-019-09792-3